2019
DOI: 10.1002/esp.4632
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of successive wildfire on soil hydraulic properties: Implications for debris flow hazards and system resilience

Abstract: Climate and land use changes have led to recent increases in fire size, severity, and/or frequency in many different geographic regions and ecozones. Most post-wildfire geomorphology studies focus on the impact of a single wildfire but changing wildfire regimes underscore the need to quantify the effects of repeated disturbance by wildfire and the subsequent impacts on system resilience. Here, we examine the impact of two successive wildfires on soil hydraulic properties and debris flow hazards. The 2004 Nutta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 57 publications
1
26
0
Order By: Relevance
“…Soil burn severity, also referred to here more generally as burn severity, is likely to play a role in the detachment and transport of PyC because the magnitude of wildfire‐induced effects on hydrologic and geomorphic systems is known to be dependent on soil burn severity (Moody et al., 2013). Soil hydraulic properties, including saturated hydraulic conductivity, play a strong role in determining the duration and intensity of rainfall required to generate runoff and have been shown to depend on burn severity (McGuire & Youberg, 2019; Moody et al., 2016). Infiltration capacity is generally lower in areas burned at moderate or high severity relative to nearby areas that are unburned or burned at low severity (Ebel & Martin, 2017; McGuire & Youberg, 2020; Moody et al., 2016; Robichaud, 2000; Robichaud et al., 2016), though soils burned at moderate and high severity are occasionally characterized by increased saturated hydraulic conductivity (Raymond et al., 2019) and decreased soil water repellency (Pierson, Robichaud, Moffet, Spaeth, Williams, et al., 2008; Tessler et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Soil burn severity, also referred to here more generally as burn severity, is likely to play a role in the detachment and transport of PyC because the magnitude of wildfire‐induced effects on hydrologic and geomorphic systems is known to be dependent on soil burn severity (Moody et al., 2013). Soil hydraulic properties, including saturated hydraulic conductivity, play a strong role in determining the duration and intensity of rainfall required to generate runoff and have been shown to depend on burn severity (McGuire & Youberg, 2019; Moody et al., 2016). Infiltration capacity is generally lower in areas burned at moderate or high severity relative to nearby areas that are unburned or burned at low severity (Ebel & Martin, 2017; McGuire & Youberg, 2020; Moody et al., 2016; Robichaud, 2000; Robichaud et al., 2016), though soils burned at moderate and high severity are occasionally characterized by increased saturated hydraulic conductivity (Raymond et al., 2019) and decreased soil water repellency (Pierson, Robichaud, Moffet, Spaeth, Williams, et al., 2008; Tessler et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…One of the largest threats to life and infrastructure after a wildfire in steep mountainous terrain is post‐fire debris flows. Several works in the special issue focus on debris flow hazards (McGuire & Youberg, 2019; Raymond et al 2020; Tillery & Rengers, 2020). Raymond et al (2020) monitored debris flow activity in five burned watersheds and demonstrated that rainfall intensity‐duration thresholds for debris flow initiation are consistent with the rainfall intensity required to exceed a critical water discharge.…”
Section: Special Issue Advancesmentioning
confidence: 99%
“…In particular, they found that debris flows on unburned slopes were typically initiated from shallow landslides while debris flows on burned slopes initiated from dispersed runoff. McGuire and Youberg (2019) focused on exploring the impacts of successive fires on debris flow processes. They used a hydrologic model, with soil hydraulic properties constrained from field measurements, to illustrate how areas that burned at moderate severity in 2004 and low severity in 2017 were likely to be more vulnerable to debris flows relative to areas that were unburned in 2004 and burned at low severity in 2017.…”
Section: Special Issue Advancesmentioning
confidence: 99%
See 1 more Smart Citation
“…Wildfire is a disturbance that is becoming more impactful as warmer temperatures, longer fire seasons, and invasive species help promote increases in fire size and frequency (Abatzoglou & Williams, 2016; Fusco et al., 2019; Miller & Safford, 2012; Pausas & Fernández‐Muñoz, 2012; Westerling et al., 2006). Wildfire can influence soil characteristics, including soil hydraulic properties (McGuire & Youberg, 2019; Moody et al., 2016) and erodibility (Moody et al., 2005; Wagenbrenner et al., 2010) as well as ground and vegetation cover (Stoof et al., 2015). Disturbance caused by wildfire typically results in increased runoff and erosion (Moody et al., 2013; Shakesby & Doerr, 2006), with debris flows being one of the more extreme geomorphic responses observed in recently burned landscapes (Cannon et al., 2001; Gabet & Bookter, 2008; Kean et al., 2011; Meyer & Wells, 1997; Nyman et al., 2011).…”
Section: Introductionmentioning
confidence: 99%